Natural history of multiple meningiomas - Wong, Ricky H. (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Asymptomatic solitary meningiomas are typically managed with clinical and radiographic follow-up. Multiple meningiomas represents a clinical entity distinct from solitary meningiomas and can be sporadic, radiation-induced, associated with neurofibromatosis, or exhibit other familial inheritance. The growth rate for multiple meningiomas is not known and therefore management of these complicated patients can be difficult. METHODS: A retrospective chart review was performed on 12 patients with a total of 55 meningiomas. Patients with neurofibromatosis were not included. Serial enhanced magnetic resonance imaging was used to determine tumor growth rates. Treatment history was also reviewed and included for analysis. RESULTS: Analysis of all 55 tumors demonstrated an average rate of growth of 0.46 cm(3)/year (range: −0.57-2.94 cm(3)/year). In the 23 tumors that received no treatment, the average rate of growth was 0.34 cm(3)/year (range: −0.03-1.8 cm(3)/year). Ten of the 23 tumors that received no treatment had no history of cranial irradiation. This group demonstrated a growth rate of 0.44 cm(3)/year (range: −0.01-1.8 cm(3)/year). Linear regression analysis did not yield any significant relationship between tumor burden and rates of growth. CONCLUSION: Tumor growth rates in patients with multiple meningiomas did not appear to be higher than reported rates for incidentally found solitary meningiomas. As such, asymptomatic multiple meningioma patients should be managed with clinical and radiographic follow-up.